Effects of low temperature stress on photosynthetic characteristics and antioxidant defense system of flue-cured tobacco - Din, Najam-Ud-; Ye, Weiguo; Chen, Jianjun; Deng, Shiyuan; Zhong, Xianyun; Chen, Yanbing (Frontiers in Plant Science, 2025)
Extreme low-temperature (LT) events, exacerbated by climate change, are increasingly threatening China’s tobacco harvest. This study examines the impact of LT stress on growth biomarkers, antioxidant enzyme activities, and physiological parameters in two tobacco varieties, K326 and Huayan06. Under LT conditions, Huayan06 showed reduced stomatal conductance under LT conditions and a significantly lower PN than K326. Both varieties exhibited an initial increase followed by a decrease in intercellular CO2 concentration and chlorophyll fluorescence parameters (Fv/Fm and ΦPSII). Notably, PSII efficiency and photochemical quenching declined sharply when temperatures dropped below 12°C and 16°C. The maximal photochemical efficiency and PN decreased within the first 6–12 hours. K326 leaves displayed higher conductivity and malondialdehyde (MDA) content than Huayan06, indicating more significant LT-induced damage. The ascorbic acid (ASA) and dehydroascorbic acid (DHA) contents varied between the varieties, with Huayan06 showing more resilience. Huayan06 also exhibited a stable glutathione (GSH) content and higher antioxidant enzyme activities superoxide dismutase (SOD), monodehydroascorbate reductase (MDAR), dehydro-ascorbate reductase (DHAR) and ASA during the initial hours of LT exposure, though these declined later. In contrast, K326 showed a substantial rise in DHA and lower GSH levels over time. RuBPase and FDPase activities were significantly reduced under LT treatment. Huayan06 experienced a 44.2% reduction in dry matter accumulation, compared to a 66.4% reduction in K326, demonstrating Huayan06’s superior capacity for dry matter production and resistance to LT stress.